Pengaruh Celebrity Endorser dan Brand Image Terhadap Keputusan Pembelian Scarlett Whitening - Elsya Medita Aurelia Putri; Asep Maulana (Jurnal Ilmiah Wahana Pendidikan, 2022)
The Influence Of Celebrity Endorser And Brand Image On PurchasingDecision Of Scarlett Whitening. Thesis of Management Sudy Program,Faculty of Economics, University of Singaperbangsa Karawang. Thepurpose of this study is to find out, analyse, and explain the description ofeach variabel, the magnitude of the relationship between CelebrityEndorser of Scarlett Whitening, and the amount of influence partially andsimultaneously Celebrity Endorser and Brand Image on PurchasingDecisions of Scarlett Whitening. By using quantitative methods and usingdescriptive analysis and verification. The analysis tool used is path analysis(path analysis). Samples taken were 150 respondents. Data collectiontechniques used are literature and field data collection by distributing usedare literature and field data collection by distributing questionnaires online.The results showed that Celebrity Endorser and Brand Image have a strongrelationship. Celebrity Endorser and Brand Image have a positive andsignificant effect on Purchasing Decision.